Hypoxia Promotes the In Vitro Proliferation of Buffalo Spermatogonial Cells by Increasing Lactate and H3K18la Lactylation Levels - Mengqi Li; Yanyu Ma; Shenzhi Wang; Haiying Zheng; Chunyan Yang; Anqin Duan; Benliang Zhou; Jianghua Shang; Xingwei Liang; Xiaogan Yang (Cells)
Hypoxia benefits the proliferation and maintenance of animal spermatogonial cells; however, the underlying mechanism remains incompletely understood. This study aims to investigate the role and mechanism of the hypoxia–glycolysis–histone lactylation axis in the proliferation of buffalo spermatogonial cells (bSCs). bSCs were cultured under different oxygen concentrations to observe changes in cell proliferation. RNA-seq was used to analyze gene expression and signaling pathways. Changes in lactylation were monitored, and CUT&Tag-seq was utilized to determine the regulatory effects of lactylation on gene expression. The glycolytic pathway was regulated to validate the results of the bioinformatic analysis. Oxygen concentrations between 2.5% and 10% support the proliferation of bSCs, with 5% having the most pronounced effect. An amount of 5% oxygen significantly increased the proliferation and pluripotency of bSCs while also promoting glycolysis and lactylation. Inhibition of glycolysis eliminated the proliferative effects of hypoxia. By analyzing genes associated with the key lactylation site H3K18la using CUT&Tag technology, we found that it is closely linked to genes involved in the regulation of proliferation. After inhibition of HK-2 expression, cell proliferation, H3K18la expression, and the expression of these target genes were all suppressed. Hypoxia promotes the proliferation of bSCs via activation of glycolysis, leading to an increase in H3K18la and altered expression of its target genes.